Understanding and Predicting Monetary Policy Framework Choice - Megan Sullivan (Heriot-Watt University, Department of Accountancy, Economics, and Finance, 2024)
This paper investigates the determinants of countries' choice of monetary policy frameworks (MPF) for emerging and developing countries. Countries make different MPF choices and we think it is because they have different country-level characteristics (e.g. democratic strength and trade networks). By covering 87 countries from 1985-2017, we investigate the role these characteristics play in predicting MPF choice. A highlight of this paper is that it uses a tailored variable to measure the volume of trade with a network that pegs to an anchor currency. We find that a country is significantly more likely to choose an exchange rate MPF when the volume increases. The model used in this paper correctly predicts 74% of MPF choice when done via a cross-validation method. This paper enables policymakers to see which MPF countries similar to their own have chosen, and they can decide if it is suitable for them, too.
Keywords: E42; E52; E58; F40; 330; Inflation targeting; central bank independence; trade networks; cross-validation